Impact of hours worked by a urologist prior to performing ureteroscopy on its safety and efficacy. (2nd January 2016) - Seklehner, Stephan; Heißler, Ortwin; Engelhardt, Paul F.; Hruby, Stephan; Riedl, Claus
Abstract: Objective: The aim of this study was to evaluate the impact of hours worked by a urologist before performing ureteroscopy on its safety and efficacy. Materials and methods: Patients treated at a single institution from January 2010 to December 2013 were analyzed. The study assessed patient, stone and surgical parameters, stone-free rates and intraoperative complications performed in three work duration categories: less than 6 h, 6–12 h and more than 12 h of urologist's work. Statistical analyses included the chi-squared test, Kruskal–Wallis test, and univariate and multivariate logistic regression analyses. Results: In total, 469 ureteroscopies were analyzed. Intraoperative complications differed non-significantly in the corresponding time categories: ureteral perforations (< 6 h 4.4%, 6–12 h 3.2%, > 12 h 7%, p = 0.46) and avulsions (all 0%). Rates for complete stone removal were 82% within the first 12 h vs 70.2% after 12 h ( p = 0.03). Corresponding partial stone-free rates were 4.1% vs 3.5% ( p = 0.83) and rates of unsuccessful ureteroscopy were 13.8% vs 26.3% ( p = 0.01). In multivariate regression analysis, patients treated after 12 h of urologist's work had a 2.4 times higher risk of an unsuccessful ureteroscopy [odds ratio (OR) = 2.4, 95% confidence interval (CI) 1.2–4.7, p = 0.001] and lower chances of complete stone removal (OR = 0.46, 95% CI 0.24–0.89, p = 0.02). The odds of ureteral perforations were similar ( p = 0.28). Conclusion: Work duration before ureteroscopy did not affect its safety. Stone-free rates decreased with increasing working time. Working time exceeding 12 h was identified as an independent risk factor for impaired stone-free rates.